2018
DOI: 10.1039/c8cp02740d
|View full text |Cite
|
Sign up to set email alerts
|

Origins of possible synergistic effects in the interactions between metal atoms and MoS2/graphene heterostructures for battery applications

Abstract: The interactions between metals and two-dimensional materials, in particular, the adsorption energies, strongly determine the performances of rechargeable batteries. Previously, it has been demonstrated that heterostructures of two dimensional (2D) materials can lead to enhanced metal adsorptions, which were ascribed to the existence of 'synergistic' effects amongst metal atoms and two different 2D materials. However, further investigations are still required to reveal the physical mechanisms behind the contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…The remarkable properties 1-3 and promising applications [4][5][6] offered by two-dimensional (2D) graphene have triggered great scientific interest to discover other 2D carbon allotropes. For example, following the success of graphene, penta-graphene, 7,8 phagraphene, 9,10 phographene, 11 ψ-graphene, 12 and θ -graphene 13 have been intensively studied for exciting applications such as in nanoelectronics and energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…The remarkable properties 1-3 and promising applications [4][5][6] offered by two-dimensional (2D) graphene have triggered great scientific interest to discover other 2D carbon allotropes. For example, following the success of graphene, penta-graphene, 7,8 phagraphene, 9,10 phographene, 11 ψ-graphene, 12 and θ -graphene 13 have been intensively studied for exciting applications such as in nanoelectronics and energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the hypothesis of the synergistic effects on the electrochemical performance of heterostructures has not been systematically studied and confirmed. Fan et al proposed the possible synergistic effects of the MoS 2 -G heterostructure by examining the adsorption and intercalation chemistry of monovalent and multivalent atoms; however, this article does not substantially describe how the synergistic effects contribute to the real system . A deep understanding of the physical and chemical properties of the MoS 2 -G heterostructure is necessary to reveal the mechanisms that govern synergistic property enhancement in these 2D heterostructures.…”
Section: Introductionmentioning
confidence: 97%
“…Fan et al proposed the possible synergistic effects of the MoS 2 -G heterostructure by examining the adsorption and intercalation chemistry of monovalent and multivalent atoms; however, this article does not substantially describe how the synergistic effects contribute to the real system. 39 A deep understanding of the physical and chemical properties of the MoS 2 -G heterostructure is necessary to reveal the mechanisms that govern synergistic property enhancement in these 2D heterostructures. Various carbons, polydopamine, dimethylacetamide 4,4-bipyridine, and mesoporous carbon, have been used to expand the 2D materials interlayer, and subsequent interfacial studies have been carried out to explore ion storage at the heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, theoretical studies focus on the adsorption of either single atoms of a series of metals [23,27,24,25,21] or large nanoparticle-like structures [19,20]. In our previous study we identified that while these studies do deliver useful insights, there is a knowledge gap in the understanding of metal thin film nucleation on 2D materials.…”
Section: Introductionmentioning
confidence: 99%